1976
DOI: 10.1055/s-0028-1095625
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin (TSH) Release During Altered Adrenergic α and β Receptor Influence

Abstract: The results are summarized in the Table. Typical histologieal ex am pies are shown in the Figure. The morphologieal evaluation of the tissue was performed by two observers independently. Quantitative morphologieal ana• lysis of the glomerular lesions is under study. Discussion and Conclusion The results eonfirm reeent observations of inhibition or even reversal of diabetie glomerular lesions in rats after transplantation of isogeneie neonatal pancreatic tissue into the peritoneal cavity or after transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study reported by Langer et al (1980) is in support of this view. However, in other studies, neither adrenergic manipulation nor short term administration of antidepressant drugs affected TSH-release on TRH-load (Lauridsen et al (1976), Kirkegaard et al (1977), Widerlöv et al (1978». According toEhrensing et aL (1974 and Kirkegaard et al (1975) a…”
Section: Discussionmentioning
confidence: 91%
“…The study reported by Langer et al (1980) is in support of this view. However, in other studies, neither adrenergic manipulation nor short term administration of antidepressant drugs affected TSH-release on TRH-load (Lauridsen et al (1976), Kirkegaard et al (1977), Widerlöv et al (1978». According toEhrensing et aL (1974 and Kirkegaard et al (1975) a…”
Section: Discussionmentioning
confidence: 91%
“…Birk Lauridsen et al (1976) also failed to detect significant influence of isoproterenol (ß-stimulator) and propranolol on TRH-induced TSH re¬ lease. Birk Lauridsen et al (1976) also failed to detect significant influence of isoproterenol (ß-stimulator) and propranolol on TRH-induced TSH re¬ lease.…”
Section: Discussionmentioning
confidence: 94%
“…16,17 Data by Faglia et al 18 indicate that TRH mediated TSH release is inhibited by dopamine and possibly by serotonin. There are no definitive data that in humans norepinephrine has a stimulating action on the release of TRH and consequently of TSH 19 as it happens in the rat, 20,23 through ScanIon et al 24,25 lead to believe that this is the case. On the basis of these data of the literature, our findings showing an increase of PRL and STH responses, normal gonadotropins release and decrease of TSH secretion cannot be interpreted as the expression of a diminution of the dopamine effect or as an involvement of noradrenergic neurotransmission, since these situations do not explain the observed responses taken together.…”
Section: Discussionmentioning
confidence: 99%